Collaborative Governance in Localizing the Sustainable Development Goals (SDGs): A Case Study of Jakarta’s Regional Action Plan (RAD) - Widhiantari, Sari Anindita; Kurniawan, Teguh (Publikasi Indonesia, 2025)
Achieving the Sustainable Development Goals (SDGs) requires effective multi-stakeholder collaboration and localization of global targets into local development planning. This study investigates how collaborative governance is applied in the formulation and implementation of the Regional Action Plan (RAD) for SDGs in DKI Jakarta, Indonesia. Using a qualitative descriptive approach and the Collaborative Governance Regime (CGR) framework by Emerson and Nabatchi, this research combines a systematic literature review (SLR) of 22 international and national studies with empirical data from in-depth interviews and document analysis. The findings reveal that while Jakarta has formally adopted collaborative principles in its RAD SDGs process, key challenges persist in inclusivity, trust-building, and resource mobilization—especially among non-governmental stakeholders. Many engagements remain consultative rather than deliberative, and joint action capacity is limited by structural and procedural gaps. This article contributes to the emerging literature on localizing SDGs by highlighting the gaps between normative collaborative ideals and practical implementation at the local government level. It also offers policy insights on strengthening stakeholder roles, institutional arrangements, and collaborative mechanisms to improve the effectiveness of SDG governance at the sub-national scale.